Intersubband absorption in GaN nanowire heterostructures at mid-infrared wavelengths. (11th July 2018) - Ajay, A; Blasco, R; Polaczyński, J; Spies, M; Den Hertog, M I; Monroy, E
Abstract: In this paper, we study intersubband characteristics of GaN/AlN and GaN/Al0.4 Ga0.6 N heterostructures in GaN nanowires structurally designed to absorb in the mid-infrared wavelength region. Increasing the GaN well width from 1.5 to 5.7 nm leads to a red shift of the intersubband absorption from 1.4 to 3.4 μ m. The red shift in larger quantum wells is amplified by the fact that one of the GaN/AlN heterointerfaces (corresponding to the growth of GaN on AlN) is not sharp but rather a graded alloy extending around 1.5–2 nm. Using AlGaN instead of AlN for the same barrier dimensions, we observe the effects of reduced polarization, which blue shifts the band-to-band transitions and red shifts the intersubband transitions. In heavily doped GaN/AlGaN nanowires, a broad absorption band is observed in the 4.5–6.4 μ m spectral region.